Two rescues, one History: everyday racism in Australia - Stratton, Jon (Routledge, 2006)
On the same day, at different ends of Australia, two extraordinary rescues of men from extreme hardship took place. The two miners, both white and of Anglo-Celtic origin, were feted, appeared on television chat shows and became celebrities so sought after that they had to employ an agent. The three Torres Strait Islanders, members of a grouping identified as 'indigenous' in the Australian social order, who had survived 22 days at sea in an open dinghy, were, to all intents and purposes, ignored by the mainstream Australian media. They would appear to have simply gone back to their families and got on with their lives. This article tracks the discursive histories in which each event was embedded to examine how this distinction could happen and how it could be so naturalised that hardly anybody commented on the disparity of treatment. It is this taken-for-granted disparity that I am describing here as everyday racism.